Open Secrets Of American Foreign Policy. - Tullock, Gordon (World Scientific, 2007)
American foreign policy is a dynamic and often controversial field, and is currently a topic of deep interest given recent developments in the Middle East, North Korea and China. In order to understand where US foreign policy is headed, it is important to first examine where it came from. This book provides an analysis of the political, economic and military history of American foreign policy, with the aim of divulging important details that most people have either never learned or forgotten hence the phrase "open secrets". Covering events such as the attack on Pearl Harbor and the American.